The Implementation of The Open-Plan Concept In The Muslim Residential - Maysarah Bakri (Elkawnie: Journal of Islamic Science and Technology, 2021)
Abstract: Muslims have to live based on Islamic values that include domestic activity in the dwelling. However, currently, people’s paradigm shifts towards modernism and also impacts the house’s preference. Architecturally, this condition is a challenge for the architect as there is a contradiction between Islamic and modern housing. One of the different principles is the closure in the Islamic dwelling and the exposure in the open-plan practice of modern residents. This research suggests how to practice the open-plan concept in Muslim residential without ignoring Islamic house principles. The research method is descriptive qualitative which the primary data is obtained through the literature review. The open-plan concept is analyzed through the principles of Islamic dwelling. The finding shows that a semi-public area of Islamic houses such as a living room or a dining room can implement the open-plan concept. The house resident uses these rooms without providing physical and visual access to non-mahram relatives, thus maintaining family privacy. The practice implications are increasing natural lighting and natural air, flexible space occupancy, and strengthening family bonding.Abstrak: Muslim harus menjalani kehidupan berdasarkan ajaran Islam, termasuk kegiatan domestik di hunian. Namun, saat ini paradigma masyarakat berubah ke arah modern dan berdampak pada preferensi hunian. Secara arsitektur, kondisi ini merupakan tantangan bagi arsitek karena terdapat kontradiksi antara hunian Islami dan modern. Salah satu perbedaan prinsipnya adalah aspek privasi pada rumah Islami dan keterbukaan dalam bentuk open-plan di hunian modern. Penelitian ini menyarankan bagaimana menerapkan konsep open-plan pada hunian Muslim tanpa mengabaikan prinsip-prinsip rumah Islami. Metode penelitian yang digunakan adalah deskriptif kualitatif dimana data primer diperoleh melalui studi literatur. Konsep open-plan dianalisa dari perspektif prinsip hunian Islami. Hasil temuan mengindikasikan konsep open-plan hanya dapat diterapkan pada area semi-publik di hunian Islami seperti ruang keluarga dan ruang makan. Hal ini dikarenakan ruang-ruang ini hanya digunakan oleh penghuni rumah tanpa menyediakan akses fisik dan visual pada tamu/kerabat non-mahram sehingga tetap menjaga privasi keluarga. Dampak penerapan konsep ini pada zona semi-publik adalah meningkatnya cahaya alami dan sirkulasi udara pada area tersebut, fleksibilitas penggunaan ruang, dan menguatkan ikatan antar anggota keluarga.